Process evaluation of the responsible parenthood and reproductive health act (RA 10354): Local service delivery component - Michael Ralph M. Abrigo; Jerome Patrick Cruz; Zhandra C. Tam (Philippine Institute for Development Studies (PIDS), 2021)
This report presents the results of a process evaluation on the delivery of mandated services in communities by local government units (LGUs) under the Responsible Parenthood and Reproductive Health (RPRH) Law. The study, which involved an extensive desk review, focus group discussions/key informant interviews, and an online survey of LGUs, is part of a larger set of evaluations that aim to document and assess the implementation of the RPRH Law, including its governance and organizational design, financing, logistic and supply chain management, and education and communication activities. While reproductive health services are generally provided by local governments, this study documents significant disparities in various aspects of local service delivery, which may be linked to differences in the available resources available to and provided by local governments, such as in fiscal resources, local information systems, human resources, infrastructure and supply, and governance. Some documentation of RPRH services, whose provision was discontinued amidst the COVID-19 pandemic in 2020, is also furnished. The report's recommendations to improve the delivery of RPRH services span measures to build support systems for RPRH, improving service delivery, and monitoring progress at the local government level.
Keywords: 330; R.A. 10354; RPRH Law; responsible parenthood and reproductive health; local service delivery